Cucurbita maxima (Pumpkin) seeds: Scolicidal activity and preventive efficacy of its extract on experimental hydatidosis in mice - Arash Babaei; Arash Jafari; Mohammad Asadpour; Morteza Shamsi (Journal of Basic Research in Medical Sciences, 2018)
Introduction: Hydatid Disease (HD), a helminth infection with various clinical complications is a serious economic and public health concern around the world. Nowadays, different agents have been broadly applied as scolicids; these agents have several side effects on patients. Therefore, the aims of this experimental study were to evaluate the scolicidal activity of Cucurbita maxima seeds methanolic extract (ME) against protoscolices of hydatid cyst in-vitro. Also, an in vivo assay was designed to prove the preventive effects of the extract. Materials and methods: For this work, Two different concentrations (25 and 50 mg/ml) of the C. maxima seeds ME were used in various exposure times (10, 20, 30, 40, 50, and 60 min). Additionally, thirty mice were infected intraperitoneally by injection of 1000 viable protoscolices and were divided into three groups with ten mice in each Group I (treated by Albendazole), group II (received 50 mg/ml of C. maxima seeds ME) and group III (untreated controls). Results: Overall, C. maxima seeds ME exhibited signiﬁcant scolicidal effects in compared with control group (P<0.05). At a concentration of 50 mg/ml, the mortality percentage increased to 84.7%, 96.1% and 100% after 40, 50 and 60 minutes, respectively. Also, the obtain data in necropsy demonstrated that C. maxima seeds ME have an inhibitory effect on the hydatid cyst development. No hydatid cyst formation observed in mice treated with C. maxima seeds ME (50 mg/ml) versus control group which hydatid cyst occurred in 6 (from 10) mice. Conclusion: The current investigation indicated that applying C. maxima seeds ME could be considered as a potential scolicidal agent due to being economical, safer and non-toxic compared to the reference chemical drugs. However, further studies on probably active compounds and also to the determination of its mode of action on parasites are required.